Respuesta :
Answer:
x = 1 and y = 4
Step-by-step explanation:
5x+2y+2x+6y = 39
7x+8y = 39
Trial and error method:
the answer that satisfies the equation are: x = 1 and y = 4
Hope this helps.
Good Luck
Answer:
(1, 4 )
Step-by-step explanation:
Given the 2 equations
5x + 2y = 13 → (1)
2x + 6y = 26 → (2)
Multiplying (1) by - 3 and adding to (2) will eliminate the term in y
- 15x - 6y = - 39 → (3)
Add (2) and (3) term by term to eliminate y
- 13x = - 13 ( divide both sides by - 13 )
x = 1
Substitute x = 1 into either of the 2 equations and evaluate for y
Substituting into (1)
5(1) + 2y = 13
5 + 2y = 13 ( subtract 5 from both sides )
2y = 8 ( divide both sides by 2 )
y = 4
Solution is (1, 4 )